Large-scale genetic analysis reveals mammalian mtDNA heteroplasmy dynamics and variance increase through lifetimes and generations - Burgstaller, Joerg P; Kolbe, Thomas; Havlicek, Vitezslav; Hembach, Stephanie; Poulton, Joanna; Piálek, Jaroslav; Steinborn, Ralf; Rülicke, Thomas; Brem, Gottfried; Jones, Nick S; Johnston, Iain G (Nature communications, 2018)
Vital mitochondrial DNA (mtDNA) populations exist in cells and may consist of heteroplasmic mixtures of mtDNA types. The evolution of these heteroplasmic populations through development, ageing, and generations is central to genetic diseases, but is poorly understood in mammals. Here we dissect these population dynamics using a dataset of unprecedented size and temporal span, comprising 1947 single-cell oocyte and 899 somatic measurements of heteroplasmy change throughout lifetimes and generations in two genetically distinct mouse models. We provide a novel and detailed quantitative characterisation of the linear increase in heteroplasmy variance throughout mammalian life courses in oocytes and pups. We find that differences in mean heteroplasmy are induced between generations, and the heteroplasmy of germline and somatic precursors diverge early in development, with a haplotype-specific direction of segregation. We develop stochastic theory predicting the implications of these dynamics for ageing and disease manifestation and discuss its application to human mtDNA dynamics.
Keywords: DNA Copy Number Variations; Animals; Female; Age Factors; Mitochondria; DNA, Mitochondrial; Genome, Mitochondrial; ženské pohlaví; Datasets as Topic; Oocytes; variabilita počtu kopií segmentů DNA; věkové faktory; Mice; oocyty; genom mitochondriální; myši; Models, Animal; mitochondrie; datové soubory jako téma; Haplotypes; mitochondriální DNA; zvířata; haplotypy; Mice, Inbred C57BL; modely u zvířat; myši inbrední C57BL